Penerapan Model Case Based Learning (CBL) Dalam Pembelajaran Menulis Teks Negosiasi Pada Peserta Didik Kelas X SMK Mataram Semarang Tahun Pelajaran 2023/2024 - Pramesthi Ode Majendra; Siti Ulfiyani; Arisul Ulumuddin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
In the latest curriculum, Indonesian language learning is oriented towards text-based learning. Therefore, students are invited to be able to produce various types of texts according to the material taught. The purpose of this study is to describe the application of the case-based learning model in the case-based learning (CBL) learning model in the Indonesian language subject of writing negotiation texts for class X students at SMK Mataram Semarang in the 2023/2024 academic year, the method used is descriptive qualitative method. This research focuses on the differences after the application of the case-based learning (CBL) model by using observation data, interviews with educators and students and documentation. As for data analysis techniques using descriptive by displaying the results of observations, the results of interviews with educators and students, student learning outcomes in the form of writing results and documentation such as learning documentation based on the steps in the application of the case-based learning (CBL) model and several other supporters. The results obtained after the application of this learning model are that students can have scores above the KKM and can also write independently the negotiation text that has been made in accordance with the linguistic rules.The conclusion based on the results of this study is that the application of the case base learning (CBL) model in class X Boga 1 SMK Mataram Semarang in the 2023/2024 academic year can be applied as an effective learning model to make students in writing negotiation text. In addition, this application can also add alternative learning for educators.